Students’ Grammatical Error Analysis in Speaking - REFA ANJENG SARI (Edukasi, 2018)
The purposes of this research were to find out the kinds of students’ grammatical error, and to figure out the dominant kind of grammatical error in speaking. The research design was descriptive research. The participant of this research was students of State Islamic University in Palembang, South Sumatera. The purposive sampling method was used to choose 12 participants; three students was taken from category of high, medium, and low score in speaking class. The collection of data used documentation by recording student’s speaking performance. The data were analyzed by using Linguistic Category Classification from Politzer and Ramirez. Based on the result of data analysis, 12 kinds of grammatical errors were found. The dominant kind of grammatical error was about number. The lowest percentages were about third person singular incorrectness and comparative adjective/adverb incorrectness.